Analysis Of Factors Affecting The Consumption Of Fruit And Vegetables For Student Of Agribusiness Major, University Of Muhammadiyah Malang - Ary Bakhtiar; M. Roja Afwihi; harpowo harpowo; Rahmad Pulung Sudibyo (JASc (Journal of Agribusiness Sciences), 2020)
Fruits and vegetables are agricultural commodities that are often consumed by the community in meeting their basic needs.  Student consumption patterns tends to be less in consuming fruits and vegetables because they are starting to be displaced by fast food.  The aim of this study was to determine the effect of socio-economic factors, knowledge, and social environment as well as the most influential factors on fruit and vegetable consumption for students of the Department of Agribusiness. This research was conducted purposively at the University of Muhammadiyah Malang.  The sampling method uses simple random sampling with 90 respondents.  The analytical method uses quantitative descriptive analysis and data analysis uses multiple linear regression test.  The results of this study indicate that social, economic, knowledge, and social environment factors simultaneously have a significant effect on fruit and vegetable consumption for students of the Department of Agribusiness, University of Muhammadiyah Malang.  Partially socioeconomic factors did not significantly influence fruit and vegetable consumption for students of the Department of Agribusiness, University of Muhammadiyah Malang.  This can be because students prefer more fast food that is practical and can be directly eaten compared to fruits and vegetables that must be peeled and washed before consuming them.  Social environmental factors have the greatest influence on fruit and vegetable consumption for students of the Department of Agribusiness, University of Muhammadiyah Malang.